Pengaruh Struktur Kepemilikan, Environmental, Social, and Governance (ESG), dan Inovasi Hijau terhadap Nilai Perusahaan - Monika Oktafiani; Indah Oktari Wijayanti (Jurnal Literasi Akuntansi, 2026)
This study examines the effect of ownership structure, ESG, and green innovation on firm value in companies listed on the ESG Leaders index from 2021 to 2024. Firm value is measured using Tobin's Q ratio. A quantitative approach with purposive sampling was adopted. Based on predetermined criteria, 17 companies were selected, yielding 68 observations. Data were collected from annual reports, sustainability reports, and ESG risk scores from the IDX ESG Leaders index. Multiple linear regression analysis was performed using SPSS. The results indicate that institutional ownership has no positive effect on firm value, ESG has a significant positive effect, and green innovation has no positive effect. This study contributes to the literature by examining the determinants of firm value and advocating for enhanced reporting standards and broader implementation of sustainable practices, which may inform policy development to advance sustainable finance in Indonesia.